Kajian Estimasi Variabel Pemudik Lebaran di Pulau Jawa Tahun 2010 dan 2011 Dengan Survei Rumah Tangga - Siahaan, L. Denny (Warta Penelitian Perhubungan, 2011)
Homecoming, called "mudik" in bahasa, at Lebaran is a culture in Indonesia to visit the family at the hometmvn. Hence, it needs bigger transportation capacity than usual. Infrastructure planning for all transportation mode needs the prediction of travelers number, origin and destination of travelers, the utilization preference of all transportation mode, the distribution of travelers per day as the basic availability of transport infrastructure and the prediction of economic effects by the travelers to the local destination. Whereas, there was household survey at 6 big cities in Java Island i.e Jabodetabek (Jakarta, Bogar, Depok, Tangerang and Bekasi), Serang, Bandung, Semarang, Yogyakarta, and Surabaya as the origin of travelers to five provinces destination within Java Island (excluded DKI Jakarta) and outside Java Island. The result of survey analysis from 34.3 million citizen at big cities in 2010 with 6,580 household samples which consist of 22,949 respondents found that 23.9% travelers, using cars 27%, buses 40%, motorcycles 14%, trains 12%, ships 1 %, airplanes 3%, and others 3%. The peak time of travelers held on the first, second, and third day before Lebaran and the seventh day after Lebaran. The economic effects from the travelers of five provinces approximately three trillion from the travelers.Keywords: travelers, transportation and lebaran economic